Modelling traffic-induced multicomponent ultrafine particles in urban street canyon compartments: Factors that inhibit mixing. (July 2018) - Zhong, Jian; Nikolova, Irina; Cai, Xiaoming; MacKenzie, A. Rob; Harrison, Roy M.
Abstract: This study implements a two-box model coupled with ultrafine particle (UFP) multicomponent microphysics for a compartmentalised street canyon. Canyon compartmentalisation can be described parsimoniously by three parameters relating to the features of the canyon and the atmospheric state outside the canyon, i.e. the heterogeneity coefficient, the vortex-to-vortex exchange velocity, and the box height ratio. The quasi-steady solutions for the two compartments represent a balance among emissions, microphysical aerosol dynamics (i.e. evaporation/condensation of semi-volatiles, SVOCs), and exchange processes, none of which is negligible. This coupled two-box model can capture significant contrasts in UFP number concentrations and a measure of the volatility of the multi-SVOC-particles in the lower and upper canyon. Modelled ground-level UFP number concentrations vary across nucleation, Aitken, and accumulation particle modes as well-defined monotonic functions of canyon compartmentalisation parameters. Compared with the two-box model, a classic one-box model (without canyon compartmentalisation) leads to underestimation of UFP number concentrations by several tens of percent typically. By quantifying the effects of canyon compartmentalisation, this study provides a framework for understanding how canyon geometry and the presence of street trees, street furniture, and architectural features interact with the large-scale atmospheric flow to determine ground-level pollutant concentrations. Graphical abstract: Image 1 Highlights: Ultrafine particle multicomponent microphysics is coupled with a 2-box canyon model. Significant contrasts in particle number concentrations in the canyon are captured. Particle number concentrations vary across modes as functions of canyon parameters. A one-box model would underestimate ground-level particle number concentrations. Abstract : Effects of canyon compartmentalisation on ultrafine particle (UFP) number concentrations and volatility are revealed by the two-box model coupled with UFP multicomponent microphysics.